Evolution may come with a price: analyzing user reviews to understand the impact of updates on mobile apps accessibility - Dos Santos, Paulo Sérgio Henrique; Oliveira, Alberto Dumont Alves; De Jesus, Thais Bonjorni Nobre; Aljedaani, Wajdi; Eler, Marcelo Medeiros (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Mobile applications are constantly updated to adapt to evolving user and environment requirements. As changes are successively implemented to promote user satisfaction, the complexity of mobile apps increases, and overlooked quality aspects (e.g. privacy, security, power consumption) may decline if counter-measures are not adopted. In this paper, we analyzed accessibility reviews of mobile apps to show evidence that updates may introduce barriers that make the app less accessible than its previous version according to users' perceptions. Our results show that accessibility barriers reported by users mostly include incompatibility with screen readers, the removal of accessibility features (e.g. color scheme or font customization), small font sizes and widgets, and incompatibility with the device's accessibility configuration. The accessibility barriers impact the users considering different levels: i) perception: an inability or difficulty to see, read or distinguish interface elements due to their small size or color; ii) understanding: the inability or difficulty to navigate, access and interpret information; iii) operation: the inability of difficulty to perform tasks such as adding items to the cart, reading or sending messages, and booking a ride; iv) and physical reactions, such as eyestrain, vertigo, and headache. The sentiments expressed by users are generally negative, including frustration, disappointment, and sometimes a sense of discrimination against people with disabilities. The results of our study raise an alert to organizations and developers that they should implement measures to avoid introducing accessibility barriers while they add new features to their mobile apps.